2019
DOI: 10.1111/imb.12615
|View full text |Cite
|
Sign up to set email alerts
|

The role of G protein‐coupled receptor‐related genes in cytochrome P450‐mediated resistance of the house fly, Musca domestica (Diptera: Muscidae), to imidacloprid

Abstract: Ninety‐four putative G protein‐coupled receptors (GPCRs) were identified in the Musca domestica genome. They were annotated and compared with their homologues in Drosophila melanogaster. Phylogenetic analyses of the GPCRs from both species revealed that several family members shared a closer relationship based on the domain architecture. The expression profiles of these genes were examined by quantitative real‐time PCR amongst three strains of the house fly, a near‐isogenic line strain with imidacloprid resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…quinquefasciatus, around 115 GPCR genes have been identified, with 52 belonging to Class A (the rhodopsin-like family), 4 to Class B (the secretin-like family) and the rest not been classified [42]. For Musca domestica, around 94 genes have been identified as GPCR genes, 55 of which are classified as Class A (the rhodopsin-like family), 27 are classified as Class B (the secretin-like family), 4 are classified as Class C (the metabotropic glutamate-like family) and the rest are still unclear [72] (Table 1, Figure 1). [72] In addition to the insects above that have been extensively studied, GPCRs from several other insect species have also been identified and annotated.…”
Section: Classification Systems Used In Characterizing Gpcrsmentioning
confidence: 99%
“…quinquefasciatus, around 115 GPCR genes have been identified, with 52 belonging to Class A (the rhodopsin-like family), 4 to Class B (the secretin-like family) and the rest not been classified [42]. For Musca domestica, around 94 genes have been identified as GPCR genes, 55 of which are classified as Class A (the rhodopsin-like family), 27 are classified as Class B (the secretin-like family), 4 are classified as Class C (the metabotropic glutamate-like family) and the rest are still unclear [72] (Table 1, Figure 1). [72] In addition to the insects above that have been extensively studied, GPCRs from several other insect species have also been identified and annotated.…”
Section: Classification Systems Used In Characterizing Gpcrsmentioning
confidence: 99%
“…An exploration of GPCRs in Tribolium castaneum indicated mth is also important for larval molt and metamorphosis (Bai, Zhu, Shah, & Palli, 2011). Moreover, mth gene mutation led D. melanogaster to become tolerant to dichlorvos (Pandey et al, 2015), but insect response to insecticide exposure was also altered with changes in the levels of mth expression (Cao et al, 2019; Li et al, 2015; Lucas et al, 2019; Ma, Zhang, You, Zeng, & Gao, 2020). Similarly to the early discussed synergism of ABCCs and phase II conjugation enzymes in insect response to insecticide exposure, mth is co-expressed with the phase I detoxification P450 enzymes, contributing to insect resistance to insecticides (Cao et al, 2019; Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that pathogen vectors have been evolving rapidly in response to the selective pressure exerted by over a century by insecticide use, novel chemicals must be developed to reduce the incidence of resistance. Accordingly, several studies have demonstrated that some insect GPCRs and their intracellular downstream pathways are highly associated with pesticide resistance [111,[140][141][142]. In Culex quinquefasciatus, 115 GPCRs and GPCR-related genes were studied in both resistant and susceptible strains to detect insecticide resistance-linked candidates.…”
Section: Opportunities Provided By Targeting Insect Gpcrs Providesmentioning
confidence: 99%
“…Repression of these GPCRs also caused the downregulation of certain insecticide resistance‐linked P450 genes [140]. Recently, a study on Musca domestica discovered an upregulated GPCR gene called LOC101899380 responsible for enhanced tolerance against imidacloprid and elevated expression of P450 genes in near‐isogenic lines with imidacloprid resistance (N‐IRS) [142]. Further bioinformatic analysis revealed that LOC101899380 shares homology with Methuselah‐like 10 (Mthl10) in D. melanogaster .…”
Section: Opportunities Provided By Targeting Insect Gpcrs Providesmentioning
confidence: 99%
See 1 more Smart Citation